Institutional and process dimensions of policy styles: key insights - Howlett, Michael; Tosun, Jale (The Routledge handbook of policy styles, 2021)
In this concluding chapter, we give an overview of the analytical value of each of the individual contributions to this volume. Being aware that every research has its limitations, in the second section we allude to venues for future research that can continue to build on aspects we consider still not to have been adequately clarified or discussed in this volume. In a last step, we offer some general concluding remarks. Overall, this chapter shows that institutional and process styles are a useful way to advance the state of research on the original formulation of national policy styles. This new perspective offers a way to develop a more nuanced conceptualization of “styles”, which goes hand in hand with fresh theoretical perspectives. However, to seize the full potential of this emerging research agenda, it appears important to engage in empirical investigations, which then feed back to the conceptualization of the “styles” concept and the corresponding theoretical arguments on how they emerge and why they change or persist.
Gesehen am 14.06.2023